Quantum Many-Body Physics of Ultracold Molecules in Optical Lattices Models and Simulation Methods - Wall, Michael L. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
This thesis investigates ultracold molecules as a resource for novel quantum many-body physics, in particular by utilizing their rich internal structure and strong, long-range dipole-dipole interactions. In addition, numerical methods based on matrix product states are analyzed in detail, and general algorithms for investigating the static and dynamic properties of essentially arbitrary one-dimensional quantum many-body systems are put forth. Finally, this thesis covers open-source implementations of matrix product state algorithms, as well as educational material designed to aid in the use of understanding such methods.